A Subanesthetic Dose of Isoflurane during Postconditioning Ameliorates Zymosan-Induced Neutrophil Inflammation Lung Injury and Mortality in Mice. (27th November 2013) - Wang, Hui; Fan, Jing; Li, Nan-lin; Li, Jun-tang; Yuan, Shi-fang; Yi, Jun; Wang, Ling; Chen, Jiang-hao; Lv, Yong-gang; Yao, Qing; Wang, Ting; Wang, Yu-cai; et al.
Abstract : Anesthetic isoflurane (ISO) has immunomodulatory effects. In the present study, we investigated whether a subanesthetic dose of ISO (0.7%) protected against zymosan (ZY) induced inflammatory responses in the murine lung and isolated neutrophils. At 1 and 6 hrs after ZY administration intraperitoneally, ISO was inhaled for 1 hr, and 24 hrs later, lung inflammation and injury were assessed. We found that ISO improved the survival rate of mice and mitigated lung injury as characterized by the histopathology, wet-to-dry weight ratio, protein leakage, and lung function index. ISO significantly attenuated ZY-induced lung neutrophil recruitment and inflammation. This was suggested by the downregulation of (a) endothelial adhesion molecule expression and myeloperoxidase (MPO) activity in lung tissue and polymorphonuclear neutrophils (b) chemokines, and (c) proinflammatory cytokines in BALF. Furthermore, ZY-induced nuclear translocation and DNA-binding activity of NF- κ B p65 were also reduced by ISO. ISO treatment inhibited iNOS expression and activity, as well as subsequent nitric oxide generation. Consistent with these in vivo observations, in vitro studies confirmed that ISO blocked NF- κ B and iNOS activation in primary mouse neutrophils challenged by ZY. These results provide evidence that 0.7% ISO ameliorates inflammatory responses in ZY-treated mouse lung and primary neutrophils.